POLLUTION CONTROL AND PESTICIDES - Boltaeva K.SH (TADQIQOTLAR.UZ, 2024)
Abstract: When making CFF nitrogen consumption of soil resources in the year of its operation increases in the second year (aftereffects) decreases unproductive nitrogen losses from CFF markedly lower than urea. CFF raises productivity Artemisia leucodes Schrenk. In field experiments, conducted in the irrigated typical gray soils and debris, the harvest was bigger by 10-30% compared to the control. The research results point to a definite advantage of using a slow acting carbamide- formaldehyde fertilizers (CFF) than urea and ammonium nitrate in reducing environmental pollution harmful to the body remains of the fat It was found that the use of slow acting . Urea-formaldehyde fertilizer is particularly important in conditions of saline soils with shallow groundwater where significant nitrogen losses occur as a result of leaching of nitrates into the groundwater. It was revealed that a higher content of nitrates in the soil when making nitrogen fertilizer as ammonium nitrate and urea lead to a significant loss of battery sizes that reach considerable values. As a result, there are a number of issues surrounding pollution as the most dangerous are increasingly finding the nitrates in the soil. It should be noted that not only accumulate nitrate in the soil - soil, ground water, but higher than allowable standards accumulate in food and feed, thus enters the body of animals and humans